The Swot Analysis Of Sharia Fintech Potential In Indonesia: Nvivo Approach Study And Literature Review - Faris, Sukron; Slamet, Slamet; Prajnawati, Maretha Ika; Bagaskara, Doni Yusuf (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
This study aims to determine the SWOT analysis of the potential of Sharia Fintech in Indonesia using the NVivo approach. This research uses qualitative methodology using the NVivo approach and literature review.